Présence/absence du monde rural dans la presse libérale et républicaine andalouse (1880-1892) - Danièle Bussy Genevois (Cahiers de Civilisation Espagnole Contemporaine)
From Jacques Maurice’s stated observation concerning the rural world ignorance by the andalousian press at the time of the Bourbon’s restoration, we shall examine two daily newspaper’s content, discourses and ability of political intervention (1880-1892). The two main issues we will focus on are El Defensor de Granada, and El Manifiesto, respectively founded in 1880 and 1884. The first one is considered to be rather “independent” and the second one, founded in Cadix, to be “progressive republican”. Knowing this, it invites us to examine their way of operating and the way both approached rurality. Both are trying to establish substitutive strategies of government policies. Both well aware of the rural misery as well as its archaism, and unlike Jacques Maurice thought, they do not consider the rural world an “exotic” place. Nevertheless the need to develop urban elites and the birth and establishment of the Republican party lead them both on paths where they would be either insensible or either hostile to rural anarchism. Indeed this last concept is almost nonexistent in the considered collections.